Terrorism in South Asia : impact on development and democratic process - Khatri, Sridhar K.; Kueck, Gert W.; Regional Centre for Strategic Studies (Colombo, Sri Lanka); Konrad-Adenauer-Stiftung (New Delhi, India) (Delhi : Shipra Publications, 2003)
Contributed papers presented earlier in a seminar jointly organized and sponsored by Regional Centre for Strategic Studies and Konrad Adenauer Foundation, New Delhi Office.
Keywords: Terrorism -- Economic aspects -- South Asia -- Congresses; Democracy -- South Asia -- Congresses; South Asian Cooperation -- Congresses